Counting and Sizing of Single Vesicles/Liposomes by Electrochemical Events. Issue 20 (17th July 2018) - Liu, Yang; Xu, Cong; Yu, Ping; Chen, Xuwei; Wang, Jianhua; Mao, Lanqun
Abstract: The analysis of single entities in a liquid phase by electrochemical events has received much attention in recent years due to innovations and advances in exciting electrochemical methods as well as precise manufacturing techniques. Vesicles, as a special type of entity, play an important role in biological systems. However, the soft character and complex surface chemistry of vesicles present inherent challenges for single‐vesicle analysis. This minireview mainly focuses on the theory and recent progress of single‐vesicle/liposome analysis based on electrochemical events. Three different analytical principles, namely, pore/channel translocation, microelectrode impact and nanopipette collision, are reviewed and expatiated. Not only the capabilities for size determination, vesicle/liposome counting and the electroactive quantification of the contents within vesicles/liposomes but also the specificities of vesicle/liposome or entity‐pore/electrode interactions reflected in translocation or collision events are discussed in detail. Moreover, the advantages and disadvantages of each method of single‐vesicle analysis are discussed in this minireview. Abstract : Good things come in threes : this review paper addresses the analysis of single vesicles/liposomes based on three different electrochemical events, and the advantages and disadvantages of each event are discussed.